PENGARUH MODEL LATIHAN DENGAN PERMAINAN LEMPAR DAN TANGKAP BOLA TERHADAP PENINGKATAN GERAK DASAR MANIPULATIF ANAK TUNADAKSA SEDANG KELAS V DI SDLB NEGERI KEDUNG KANDANG KOTA MALANG - Luthfi Hidayat Tulloh; Slamet Raharjo; Sapto Adi (Universitas Negeri Malang, 2017)
Abstract: The influence of the model of throwing and catching game training on improving the basic manipulative motion of children with disability while in grade V in SDLB N Kedung Kandang Malang, is a study aimed to know the model of game exercises given to the improvement of basic motion of throwing and tank manipulative. This research is a kind of quasi-experimental research using single subject research (SSR) method. To obtain valid results the researcher uses a power test instrument, precision test, endurance test.Keywords: game model, disability, throw and catch